Aplikasi Grupchat di Android Menggunakan Websocket - Hardianto, Fitri; , Dr. Ir. Bana Handaga, M.T (2015)
Chat is a network technology to send and receive messages to other user that connected in a LAN network or the internet. And now, many chat applications emerging from a web , desktop or mobile. There are many protocols that are used to building chatt applications such as IRC, MTProto, YMSG and the latest is WebSocket. WebSocket is a protocol that provides full-duplex communication channel by a single TCP, WebSocket designed for applied in a web browser, a web server and a client server application. WebSocket also support for android and IOS mobile. WebSocket very suitable for a group chat application, because the features and advantages that match wiith the characteristics of the chat, such as real-time, two-way communication that allows the server push the data from client to client, and its traffic is not too heavy. Group chat using WebSocket application in android created using Eclipse that installed Tomcat 7, Eclipse Java EE Developer Tools, JST Server Adapters, and JST Server Adapters Extensions, the Android SDK. Keywords : Android, Chatting, Websocket.